Wielka Świątynia Atona jako przestrzeń indywidualnego personalnego kultu - Sławomir Jędraszek (In Gremium. Studies in History, Culture and Politics, 2025)
One of the most fascinating and provocative figures in history is Akhenaten, who has captured the imagination like no other Egyptian pharaoh. Popularly known as a 'heretic,' King Akhenaten sought to impose his personal vision on Egypt, particularly in the city he founded, which he named Akhetaten ('the Horizon of the Aten'; modern Tell el-Amarna), and on its people by promoting the primary object of attention, the sun god Aten.The results of the latest archaeological work at the site, especially in the part of the Great Temple of Aten ('House of the Aten'), in the opinion of Barry Kemp, have provided a more diverse perspective on the true nature of King Akhenaten's Atenism.